Les catastrophes naturelles : le syndrome du 17 janvier - Moreau, Rémi (Assurances, 1995)
The two devastating earthquakes, like the one that hit Northridge (USA) on the morning of January 17, 1994 or the one that struck Kobe (Japan) on January 17, 1995, one year later, illustrate the need for both the government and the insurance industry to plan for natural catastrophes. Why do the actual damage figures far exceed initial estimates? The author comments on several reasons, including inaccurate initial seismological information, lack of interest in investigating the design of new types of structures, inadequate emergency plans, etc. Northridge and Kobe showed that planners and builders have exaggerated how quake-proof their structures are. Natural disasters in 1994 and in the first month of 1995 have increased pressure to develop a catastrophe prevision system to prevent aggravated damage.